Serum Levels of Cytokines in two ethnic groups with dengue virus infection (2008)
ABSTRACT: This study compared the serum levels of tumor necrosis factor-alpha (TNF- α), interleukin-6 (IL-6), and interferon gamma (IFN- γ) in 78 Colombian patients, from two ethnic groups, with dengue virus infection. TNF- γ levels were significantly higher in Afro-Colombians than in Mestizos and IL-6 levels were significantly higher in Mestizos than in Afro-Colombians, during the acute phase. IFN- levels were similar in both ethnic groups. Significantly higher TNF- α levels were found in Afro-Colombians than in Mestizos in both dengue fever (DF) and dengue hemorrhagic fever (DHF). The IL-6 levels were higher in Mestizos than in Afro-Colombians among patients with DF, but levels of this cytokine were higher in Afro-Colombians than in Mestizos among patients with DHF. Levels of IFN-γ were higher in patients with DHF than DF. Higher levels of these cytokines were observed in secondary infection. These results suggest that ethnicity may contribute to differences in immune responses to dengue infections.